Response of Anammox bacteria to elevated nitrogen and organic matter in pre-digested chicken waste at a long-term operated UASB reactor initially seeded by methanogenic granules. (September 2019) - Pekyavas, Goksen; Yangin-Gomec, Cigdem
Abstract: Up-flow anaerobic sludge bed (UASB) reactor originally inoculated by methanogenic granules was operated for nine months for total ammonia nitrogen (TAN) removal through anaerobic ammonium oxidation (Anammox) route with external nitrite source (NH4 :NO2  = 0.99 ± 0.19). However, bioreactor was operated at elevated TAN (330 ± 48 mg/L) and total chemical oxygen demand (tCOD) (2868 ± 378 mg/L) in diluted chicken waste digestate between 120 and 274 d with respective removals up to 57 ± 7% and 80 ± 4%. The response of microbial cultures, especially Planctomycetes (Anammox bacteria) to such influent TAN and tCOD was also investigated by high-throughput sequencing analyses. Results indicated the co-existence of denitrifying bacteria playing significant role in nitrogen removal with Anammox bacteria. Firmicutes and Bacteroidetes phyla doubled their relative abundances; however, a sharp decrease in Planctomycetes was observed. Moreover, predominant phylum changed from Proteobacteria to Firmicutes while dominance of Euryarchaeota remained constant indicating nitrogenous and organic matter contents were the most important factors dominating the bacterial community structure. Graphical abstract: Unlabelled Image Highlights: Pyrosequencing indicated co-existence of denitrifying and Anammox bacteria. Sequences related to Planctomycetes were identified, however at low abundance. The predominant phylum changed from Proteobacteria to Firmicutes. Nitrogen and organic content were important factors dominating bacterial structure. Ammonia removal of 57% was achieved at elevated nitrogenous and organic matter.